ANALISIS PELAKSANAAN SISTEM PENGENDALIAN INTERNAL PADA PROSEDUR PENERIMAAN DAN PENGELUARAN BARANG DI PT. UNISEM BATAM - Rusda Irawati; Ardhila Kamalita Satri (Politeknik Negeri Batam, 2017)
This is a descriptive qualitative research that aims to find out about the internal control system at PT. Unisem Batam. This study uses 10 speakers, for the election of speaker / researcher informants using purposive sampling and snowball sampling. The data collection technique used is interview, documentation and observation.The results obtained from this study is that implementation of the Internal Contro l System Acceptance Procedure and Expending of Goods in PT. Unisem Batam have been effective, but still has weaknesses such as, there are a lot of mistakes made as not undergo the procedure expenditures properly, still found fault placement of goods, provision of part number, incorrecly data entry at the store, and the division of tasks is definitely on receiving section.